A Randomized Pharmacokinetic Study of Generic Tacrolimus Versus Reference Tacrolimus in Kidney Transplant Recipients - Alloway, R R (Blackwell Publishing Inc, 2012)
Pharmacokinetic analyses comparing generic tacrolimus preparations versus the reference drug in kidney transplant patients are lacking. A prospective, multicenter, open-label, randomized, two-period (14 days per period), two-sequence, crossover and steady-state pharmacokinetic study was undertaken to compare twice-daily generic tacrolimus (Sandoz) versus reference tacrolimus (Prograf®) in stable renal transplant patients. AUC(0–12h) and peak concentration (C(max)) were calculated from 12 h pharmacokinetic profiles at the end of each period (days 14 and 28). Of 71 patients enrolled, 68 provided evaluable pharmacokinetic data. The ratios of geometric means were 1.02 (90% CI 97–108%, p = 0.486) for AUC(0–12h) and 1.09 (90% CI 101–118%, p = 0.057) for C(max). Mean (SD) C(0) was 7.3(1.8) ng/mL for generic tacrolimus versus 7.0(2.1) ng/mL for reference tacrolimus based on data from days 14 and 28. Correlations between 12 h trough levels and AUC were r = 0.917 for generic tacrolimus and r = 0.887 for reference drug at day 28. These data indicate that generic tacrolimus (Sandoz) has a similar pharmacokinetic profile to the reference drug and is bioequivalent in kidney transplant recipients according to US Food and Drug Administration and European Medicines Agency guidelines.